Parallel movement of the hands five unfinished longer works - Ashbery, John 1927-2017 (Ecco, an imprint of HarperCollinsPublishers, 2021)
"A stunning collection of work from beloved poet John Ashbery: his first posthumous book. Renowned for his inventive mind, ambitious play with language, and dexterity with a wide range of tones and styles, John Ashbery has been a major artistic figure in the cultural life of our time. Parallel Movement of the Hands gathers unpublished, book-length projects and long poems written between 1993 and 2007, along with one (as yet) undated work, to showcase Ashbery?s diverse and multifaceted artistic obsessions and sources, from children?s literature, cliffhanger cinema reels, silent films, and classical music variations by Beethoven?s pupil Carl Czerny to the history of early photography. Ashbery even provides a fresh and humorous take on a well-worn parable from the Gospel of Matthew. These works demonstrate that while producing and publishing the shorter, discrete poems often associated with his late career, Ashbery continued to practice the long-form, project-based writing that has long been an important element of his oeuvre. Edited and introduced by Ashbery?s former assistant poet Emily Skillings and including a preface by acclaimed poet and novelist Ben Lerner, this compelling and varied collection offers new insights into the process and creative interests of a poet whose work continues to influence generations of artists and poets with its signature intertextuality, openness, and simultaneity. A landmark publication of never-before-seen works, this book will enlighten scholars as well as new readers of one of America?s most prominent and celebrated poets."--Publisher's website
Keywords: English poetry / 21st century; American poetry / 21st century; Poetry